Metronidazole alone or with amoxicillin as adjuncts to non-surgical treatment of chronic periodontitis: a secondary analysis of microbiological results from a randomized clinical trial - Soares, Geisla M. S.; Mendes, Juliana A. V.; Silva, Maike P.; Faveri, Marcelo; Teles, Ricardo; Socransky, Sigmund S.; Wang, Xiaoshan; Figueiredo, Luciene C.; Feres, Magda (Journal of clinical periodontology, 2014)
Aim To evaluate the changes occurring in the subgingival microbial profile of subjects with generalized chronic periodontitis (ChP) treated by scaling and root planing (SRP) alone or with metronidazole (MTZ) or MTZ + amoxicillin (AMX). A secondary aim was to examine a possible added effect of chlorhexidine (CHX) to these therapies. Methods One hundred and eighteen subjects were randomly assigned to receive SRP‐only or with MTZ [400 mg/thrice a day (TID)] or MTZ + AMX (500 mg/TID) for 14 days. Half of the subjects in each group rinsed with 0.12% CHX twice a day (BID) for 2 months. Nine subgingival plaque samples/subject were analysed by checkerboard DNA–DNA hybridization for 40 bacterial species at baseline, 3, 6 and 12 months post‐therapy. Results At 12 months, the antibiotic‐treated groups harboured lower mean counts and proportions of key periodontal pathogens than the SRP group (p < 0.05). These benefits were observed at initially deep and shallow sites. Initial reductions in periodontal pathogens obtained with SRP partially rebound after 12 months. CHX rinsing enhanced the microbiological effects of the MTZ + AMX treatment in shallow sites. Conclusion The adjunctive use of MTZ and MTZ + AMX results in a greater reduction in the levels of periodontal pathogens in generalized ChP subjects compared to SRP alone.